Old Russian Calligraphy in the Context of Cognitive Transformations (Some Notes on Early Modern Monokondylia) - Tsypkin, Denis O. (Actual Problems of Theory and History of Art, 2022)
The object of our research is the process of shaping of the Early Modern person in the culture of Old Rus. The research is focused on technological turning points which are viewed basing on Old Russian writing and book culture. Any substantial change in technology is not only important as such, but also as an element of cognitive transformation. The latter consists in a systematic change of people’s skills and habits which eventually entails the society’s transition to new models, styles and strategies of thought, and world outlook. The cognitive transformation is the result of changes in skills and habits. Together they form psychological and psychophysiological contents of such transitions, shaping a ‘new’ person for a new epoch.The changes in writing and reading skills are of special interest in studying the processes of cognitive transformations. It is from this point of view that we discuss the monokondylia compositions in Russian Early Modern ABC-books on calligraphy. We analyze the function of monokondylia in shaping the skills that paved the way for development of cursive writing in Muscovy. The role of calligraphic art in the formation of the system of Russian Early Modern culture is discussed.
Keywords: ABC-books; calligraphy; medieval Russian art; Russian cursive writing; neurohistory; cognitive sciences